Pleuro-Pulmonary Blastoma: A Rare Cause of Pleural Effusion in a Young Girl - Rashid, Md Mamunur; Alam, Mohammad Fakhrul; Hasanat, Abu; Zamal, Younus; Islam, Zahidul; Rahman, Md Mostafizur (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Pleuropulmonary blastoma (PPB) is a rare, primitive primary neoplasm of the thorax that affects children. We present a case of a girl of 11 years who was admitted in National Institute of Diseases of the Chest and Hospital (NIDCH) with the complaints of high grade continued fever and shortness of breath. Initial physical examination and chest radiograph was suggestive of left sided massive pleural effusion. Along with pleural effusion, chest CT depicted a large heterogeneous mass occupying most of the left hemithorax. Computed tomography and bone scintigraphy suggested the mass to have a primary pulmonary origin. Cytologically the lesion was consistent with pleuropulmonary blastoma. Due to pleural involvement and presence of large inoperable mass, we considered chemotherapy as the first modality of treatment prior to surgery and managed thereby. DOI: http://dx.doi.org/10.3329/jbcps.v30i3.12469 J Bangladesh Coll Phys Surg 2012; 30: 173-176